Knowledge on the action to be taken and recognition of symptoms of stroke in a community: findings from the May Measurement Month 2017 blood pressure screening Programme in Malaysia - SiewMooi Ching; Yook Chin Chia; Bee Nah Chew; Man Jun Soo; Hooi Min Lim; Wan Aliaa Wan Sulaiman; Fan Kee Hoo; Mar Lar Saw; Azlina Ishak; Tharmalingam Palanivelu; Nadarajan Caruppaiya; Navin Kumar Devaraj (BMC, 2019)
Abstract Background Information regarding the knowledge on the action to be taken during stroke and good recognition of stroke symptoms is mandatory in helping to plan out educational strategies to deliver health education to the community. Methods This is a cross-sectional study of adults aged 18 and above attending a blood pressure screening program in community in conjunction with May Measurement Month 2017 in Malaysia. A structured self-administered questionnaire was given to the participants who gave verbal consent. Data analysis was done using SPSS v. 23 and multiple logistic regression was used to identify the determinants of knowledge on actions to be taken during stroke and recognition of stroke symptoms. Results Out of 4096 respondents, 82.9-92.1% of them able to recognise the common stroke symptoms. and 74.2% of the study respondents will go to hospital within 4.5 h of stroke onset. According to binomial logistic regression analyses, adults aged 45 years old and above (OR 1.39 95%CI 1.01-1.92), being Malay (OR 1.74, 95% CI 1.27-2.40), being non-smokers (OR = 2.491, 95% CI: 1.64-3.78), hypertensives (OR: 1.57, 95% CI: 1.02-2.42)and diabetics (OR: 2.54, 95% CI:1.38-4.69) are determinants of right actions to be taken during stroke. Meanwhile, respondents aged 45 years old and older (OR = 1.68, 95% CI: 1.39-2.03), being Malay (OR = 1.49, 95% CI: 1.24-1.79), hypertensive (OR = 1.32, 95% CI: 1.04-1.66) and those who had a previous history of stroke (OR = 2.25, 95% CI: 1.01-5.00) are determinants of good recognition of stroke symptoms. Conclusions The overall knowledge of stroke in our study population was good. Older age, being Malay, non-smokers, hypertensives and diabetics are determinants of right actions to be taken during stroke. Meanwhile, older age, being Malay, hypertensive and those who had a previous history of stroke are determinants of good recognition of stroke symptoms.